Transduction of baculovirus vectors to queen honeybees, Apis mellifera - Ikeda T. (2014)
The potential uses of baculovirus as a gene vector to queen honeybees were examined in this study. We used a green fluorescent protein-expressing baculovirus with wild-type envelope and two pseudotype viruses of which one overexpressed GP64 and the other expressed a virion protein of a honeybee virus on the envelope. After injection of these baculoviruses into queen pupae, infection was detected in the fat bodies, but not in the ovaries. Pupae injected with a titer of 1×105 infectious units survived to eclose, and the infection was also detected in the fat bodies of adult queen honeybees, suggesting that baculoviruses can transiently express genes in the fat bodies, and therefore, can be used for further analysis of gene functions. In addition, although the viruses examined in this study failed to express the reporter gene in the ovaries, the infection in the fat bodies suggests that baculoviruses could be potentially useful for transgenesis, if appropriately developed. © INRA, DIB-AGIB and Springer Science+Business Media B.V., 2011.